The Principle of Coherence in Serbian Constitutional Court Decisions about Uniqueness of Legal System - Hadži Stević, Brano (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Articles 4 and 194 of the Constitution of the Republic of Serbia prescribe that the legal order of Serbia is unique. Interpreting this constitutional principle, the Constitutional Court of Serbia has developed a doctrine on the distinction between systemic and ordinary laws, based on the primacy of systemic laws over ordinary ones. Ordinary law must be in accordance with the systemic law because otherwise it is unconstitutional. Explaining its position, the Constitutional Court claims that the constitutional principle from article 4 requires that all laws be in accordance (consistency) and act in the same direction (coherence). We will analyze the principle of coherence, its relationship with consistency, and then apply those insights to the doctrine of the Constitutional Court, in an effort to determine the merits of such a distinction. The main hypothesis from which the paper starts is that the Constitutional Court gives absolute primacy to the principle of unity of legal order, which we consider axiologically acceptable but unacceptable from positive law aspect, since this principle must be considered in the light of other principles, especially in the light of separation of powers.